Atravessamentos nas construções subjetivas dos/as estudantes de graduação em psicologia: potências e afecções. - Lucena, Polyana Luz de (2024)
Entering a university is a factor of great transformation for students and the context in which they live, transformations that are full of anxiogenic aspects and, in many cases, geographical change and family separation, intense routine, exhausting study hours, in addition to the institutional and social demands to which they are subjected. The illness of undergraduate students is evident in contemporary times and, given this context, a different look at them becomes urgent. With regard to Psychology graduates, there are also other specificities, as, in addition to the complaints that commonly occur in other undergraduate courses, these students experience some particularities inherent to Psychologist training, such as: direct contact with human subjectivity confronts them with their own lives, their difficulties, their conflicts, which, in turn, can generate suffering and repercussions on their future professional practice. Based on these observations, and as a psychologist in a School Service, the researcher began to inquire about the ways in which Psychology students are affected, which generate existential suffering for them, and which are evident in the massive search for assistance in School Services. Still in this direction, they are asked, more specifically, what possibilities can be offered in these spaces, in the care of these students. Based on this contextualization, the main objective of this thesis work is to map the intersections that affect the subjective constructions and existential suffering of undergraduate Psychology students and propose possibilities for listening and interventions in the School Service. Specifically, it is intended to: I. describe the field of forces that appears in the subjective constructions of these students; II. understand the addresses addressed by these students in the context of a School Service; and III. problematize how the School Service can contribute to welcoming these people. The theoretical framework has the perspective of Schizoanalysis and, as a way of supporting the field-theme object of this study, an intervention-research was carried out, of a qualitative nature and of cartographic inspiration, using the resources of interviews, the field diary and holding reflective groups. As participants, 6 (six) undergraduate Psychology students from a Public Higher Education Institution were selected, without distinction of age, gender, ethnicity, and socioeconomic status, to form a reflective group. In order to produce data in the field, participants contributed with a narrative of their experiences in the Psychology course. The analysis of the results included the emergence of significant elements and the production of meaning resulting from it. Throughout the 6 (six) sessions held, intersections were raised based on the lines of segmentarity: hard, flexible and escape, which emerged together with the analyzers (understanders) and made it possible to map how the subjectivities of these students are constructed. Themes, such as neoliberalism, which is advancing in universities; the culture of individualism and self-employment; the racism; the stigma of LGBTQIA+ people; the teacher-student relationship; the remnants left by the COVID-19 pandemic; the fragility of relationships and the excesses experienced by the current generation; the relationship with technology and digital reality, made up the mapping of the forces that affect the subjective constructions of students. Furthermore, it was sought to outline the conditions of possibility for the School Service to welcome students in their demands in search of their creative potential for transformation. Thus, it is believed that, in the research-intervention process, changes could be promoted as demands were expressed, in order to create a space of autonomy and protagonism for students, in addition to giving visibility to their psychosocial needs in the university environment, as a process of research and life was built.